A humanized mouse identifies the bone marrow as a niche with low therapeutic IgG activity - Lux, Anja; Seeling, Michaela; Baerenwaldt, Anne; Lehmann, Birgit; Schwab, Inessa; Repp, Roland; Meidenbauer, Norbert; Mackensen, Andreas; Hartmann, Arndt; Heidkamp, Gordon Frederik; Dudziak, Diana; Nimmerjahn, Falk (Cell Reports, 2014)
Genetic differences between humans and in vivo model systems, including mice and nonhuman primates, make it difficult to predict the efficacy of immunoglobulin G (IgG) activity in humans and understand the molecular and cellular mechanisms underlying that activity. To bridge this gap, we established a small-animal model system that allowed us to study human IgG effector functions in the context of an intact human immune system without the interference of murine Fc? receptors expressed on mouse innate immune effector cells in vivo. Using a model of B cell depletion with different human IgG variants that recognize CD20, we show that this humanized mouse model can provide unique insights into the mechanism of human IgG activity in vivo. Importantly, these studies identify the bone marrow as a niche with low therapeutic IgG activity.
EVALuna2:6588